In situ performance evaluation of chemical injections against rising damp: A case study in Italy. (December 2018) - Sardella, Alessandro; De Nuntiis, Paola; Rizzo, Marzia; Giosuè, Chiara; Tittarelli, Francesca; Bonazza, Alessandra
Highlights: The performance of chemical injections over time in situ was evaluated. Gravimetric method was used to measure the moisture content in walls. Treatment with silane/siloxane organic solvent based showed the better performance. Hygroscopic moisture content showed moisture sources not linked with rising damp. Abstract: Rising damp is one of the most relevant cause of deterioration in historic buildings and its presence may trigger and intensify damage processes such as biodeterioration and decohesion linked to freeze-thaw and salt crystallization cycles. Treatment against rising damp is generally advised and several products are currently available in the market, whose efficiency, durability and compatibility with building materials are unfortunately still not exhaustively verified. For a proper evaluation of these features aiming at a sustainable protection and conservation of cultural heritage, test directly on site in addition to laboratory investigations is increasingly recommended. Within this work we illustrate and discuss results obtained during a test on site for the efficiency evaluation over time of treatments against rising damp based on chemical injections performed in one of the case studies in the JPICH Project EMERISDA.